The Impact of Symbolic Interaction on Grounded Theory - Barney G. Glaser (Grounded Theory Review: An International Journal, 2005)
(Chapter 10, The Grounded Theory Perspective III: Theoretical Coding, Sociology Press, 2005) As I stated in the introduction to chapter 9, GT is a general inductive method possessed by no discipline or theoretical perspective or data type. Yet the takeover of GT by Symbolic Interaction (SI) and all the departments and institutes that SI informs and resides in is massive and thereby replete with the remodeling of GT. The literature on qualitative methodology is massive and replete with the assertion that SI is the foundation theoretical perspective of GT. GT is reported as a SI method. That GT is a general inductive method is lost.